Selective Expression of Nicotinic Receptor Sub-unit mRNA in Early Human Fetal Forebrain - Alzu’bi, Ayman; Middleham, William; Shoaib, Mohammed; Clowry, Gavin J. (Frontiers in Molecular Neuroscience, 2020)
Increasing evidence from animal and human studies indicate that exposure to nicotine during development, separated from the effects of smoking tobacco, can contribute to dysregulation of brain development including behavioural deficits. An RNAseq study of human fetal cerebral cortex demonstrated that 9 out of 16 genes for human nicotinic acetylcholine (ACh) receptor subunits are selectively expressed between 7.5-12 post-conceptional weeks (PCW). The most highly expressed subunit genes were CHNRA4 and CHNRB2, whose protein products combine to form the most ubiquitous functional receptor isoform expressed in the adult brain. They exhibited correlated expression in both RNAseq samples, and in tissue sections by in situ hybridisation. Co-localisation studies with other cortical markers suggest they are predominantly expressed by post-mitotic glutamatergic neuron precursors in both cortical plate and presubplate, rather than cortical progenitor cells or GABAergic interneuron precursors. However, GABAergic interneuron progenitor cells in the ganglionic eminences do express these sub-units. CHNRA5 also showed moderate levels of expression and again favoured post-mitotic neurons. Other subunits, e.g CHRNA7, exhibited low but detectable levels of expression. CHRN genes found not to be expressed included genes for subunits usually considered muscle specific, e.g. CHNRA1, although some muscle specific gene expression was detected, for instance CHNRB1. Although there is little or no synthesis of acetylcholine by intrinsic cortical neurons, cholinergic fibres from basal forebrain innervate the cerebral cortex from 12 PCW at the latest. Acetylcholine may have a paracrine effect on radially migrating cortical neurons and GABAergic interneuron progenitors.